MolluscaBase – announcing a World Register of all Molluscs - Bank, Ruud A.; Bieler, Rüdiger; Bouchet, Philippe; Decock, Wim; Dekeyser, Stefanie; Kroh, Andreas; Marshall, Bruce; Neubauer, Thomas A.; Neubert, Eike; Rosenberg, Gary; Sartori, André F.; Schneider, Simon; et al. (My University, 2014)
The Mollusca, second largest phylum on Earth, lack a global listing of valid names or even precise figures for the number of Recent species. The launching of MolluscaBase is intended to fill this gap, expanding the contents of the World Register of Marine Species (WoRMS) to include all marine, freshwater and terrestrial molluscs, recent and fossil. The WoRMS database, hosted at the Flanders Marine Institute (VLIZ) at Oostende, had more than 1,000,000 unique visitors in 2013 and provides the taxonomic backbone for initiatives such as Encyclopedia of Life, Catalogue of Life, and others. It currently contains more than 44,000 valid species names of Recent marine Mollusca, which are estimated to represent approximately 95% of all valid species. There is no similar global list of the freshwater and terrestrial Mollusca. It is estimated that there are about 23,000 species of land snails/slugs and about 5,000 freshwater gastropods and bivalves. The number of named fossil Mollusca is not known, but is in the same order of magnitude as that of Recent species. MolluscaBase is intended as an authoritative taxonomic database, relying only on published sources and built by taxonomic editors who are active malacologists and respond to feedback from users. Like in WoRMS, the contents should include Taxonomic hierarchy, Current name and synonymy, Literature sources, Distributions (using countries as the basic unit for land-based distributions), Fossil range (expressed in terms of the international chronostratigraphic chart) and other taxon attributes. This initiative is supported by LifeWatch, the E-Science European Infrastructure for Biodiversity and Ecosystem Research. In a first move, MolluscaBase should build on the existing WoRMS contents incorporating the contents of existing initiatives like CLEMAM (Checklist of European MArine Molusca), FreshGEN (Freshwater Gastropods of the European Neogene) and Fauna Europaea. The long term goal of filling the gaps in non-marine and fossil components of MolluscaBase needs your support! If you are a taxonomist, specializing in any group of non-marine or extinct molluscs, and wish to become a contributor to MolluscaBase, please let us know and contact the WoRMS team at info@marinespecies.org, or the corresponding author, to find your possible role in MolluscaBase!
Resumen de comunicación oral en congreso
Keywords: Moluscos